Analysis of Gene Regulatory Networks of Taro (Colocasia esculenta (L.) Schott.) Soluble Starch Synthase Based on DeGN and KASP Marker Development - Lu Jiang; Jianmei Yin; Li Wang; Xiaoyong Han; Peitong Zhang (International Journal of Genomics)
Taro (Colocasia esculenta (L.) Schott.) is an important edible and economically valuable crop that is also a source of high-quality starch. Its quality is determined by the content and proportion of amylopectin. Based on transcriptome sequencing of corms at different growth stages (T1–T6), 34,603 transcripts and 1727 novel genes with functional annotation were obtained. In total, 11,865 differentially expressed genes (DEGs) were identified among six development stages, with 3836 and 3404 DEGs in T2 versus T3 and T3 versus T4, respectively. The regulatory network of taro starch synthesis was constructed on the DeGNServer. Among three cloned soluble starch synthase (SS) genes, CeSS II might be the key gene responsible for soluble starch synthesis in taro corm. The putative transcription factor CeMyb108 might play a negative role in starch synthesis. Sanger sequencing CeSS II gene revealed a single nucleotide polymorphism (SNP) between two variety groups with high and low starch content. A kompetitive allele-specific PCR (KASP) marker, namely, CeSS II-SNP, was developed and validated in a natural population of 89 taro accessions. The starch content of the C:T group amounts to 517.45 mg/g, which is significantly (22.3%) higher than its counterpart (T:T). This newly developed marker is proved to be effective and would facilitate marker-assisted breeding for taro with high starch content.